Undiagnosed HIV Presenting with Lymphoid Interstitial Pneumonitis - Jason J. Rizqallah; Christopher T. Shah; Oladoyin Oluwole; John N. Sheagren (Case Reports in Infectious Diseases)
Undiagnosed or untreated human immunodeficiency virus infection can lead to devastating complications. We present a case of a 41-year-old woman who was found to have HIV-related lymphoid interstitial pneumonitis. LIP is uncommon, and its presentation can be quite similar to that of other chronic lung conditions. This case illustrates one of the possible protean manifestations of untreated HIV and is a sobering reminder of the need to screen all adults for HIV infection. Additionally, further invasive diagnostic testing may be required to guide therapy in patients with advanced acquired immune deficiency syndrome. This patient's LIP was likely related to long-standing unrecognized HIV disease.